Efektivitas Layanan Konseling Kelompok dalam Penelitian Terkini (2020-2025) - Elsa Yutri Melinda; Zafirah Talitha Arisyah; Rafeylah Areefa Elya; Indah Permata Sari; Noval Tri Pernando; Ratna Sari Dewi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The selection of group counseling interventions in addressing learners' problems shows high effectiveness because it utilizes group dynamics that support the development of emotional aspects, cognition, and communication skills. Group counseling has an important role in the preventive, curative, and developmental functions of learners, both in terms of mental health, social skills, academics, and career planning. Group counseling is a relevant form of counseling service to deal with learners' problems that are urgent and have similarities, and serves as a means of holistic self-development. The effectiveness of this service depends not only on productivity, but also the perspectives of counseling teachers, students, and the efficiency of implementation, all of which are influenced by the professional competence of counselors according to national standards. Effectiveness itself is understood as success in achieving service goals, which includes internal and external factors of service implementers. In its implementation, different group counseling approaches and techniques can still achieve optimal results when adjusted to the problems and needs of students. The use of the Cognitive Behaviour Therapy approach in group counseling is proven to increase participants' understanding of thoughts, emotions, and behaviors, and strengthen group interaction in depth. Strategies and innovations in counseling techniques or methods need to be adjusted to strengthen the effectiveness of the service, while participant activeness and the dynamics of social interaction are important factors in supporting the success of group counseling. Therefore, collaboration between group members is needed so that the counseling process runs smoothly and service goals can be achieved optimally.